2020
DOI: 10.7717/peerj.9022
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of determinants of performance in dressage

Abstract: As a first step in achieving an evidence-based classification system for the sport of Para Dressage, there is a clear need to define elite dressage performance. Previous studies have attempted to quantify performance with able-bodied riders using scientific methods; however, definitive measures have yet to be established for the horse and/or the rider. This may be, in part, due to the variety of movements and gaits that are found within a dressage test and also due to the complexity of the horse-rider partners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…Equestrian sports are unique among the Olympic disciplines in that they involve two athletes of different species. The skill of the rider is key to maximizing the benefits of training to produce a top performance in the competition arena [ 2 ]. In this study, we have correlated the riders’ proficiency in performing three tasks on a gymnastic ball with the quality and harmony when riding the horse, and with physiological and behavioral indices of their horse’s performance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Equestrian sports are unique among the Olympic disciplines in that they involve two athletes of different species. The skill of the rider is key to maximizing the benefits of training to produce a top performance in the competition arena [ 2 ]. In this study, we have correlated the riders’ proficiency in performing three tasks on a gymnastic ball with the quality and harmony when riding the horse, and with physiological and behavioral indices of their horse’s performance.…”
Section: Discussionmentioning
confidence: 99%
“…A published review of the equestrian literature identified functional abilities of the rider that may affect horse performance in dressage and influence the horse to achieve higher scores [ 2 ]. The rider’s ability to coordinate pelvic and trunk movements with the horse’s body movements emerged in this review as a key indicator of rider influence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations